Tumour seeding as a result of intraperitoneal perforation during transurethral resection of non-muscle invasive bladder cancer. (24th September 2014) - Cusano, Antonio; Murphy, Greg; Haddock, Peter; Wagner, Joseph
Abstract : The goals of transurethral resection of bladder tumour (TURBT) for urothelial carcinoma are pathological staging and the removal of all visible tumour tissue. Typically, a deep and extensive resection beyond the basement membrane, including some muscularis propria, is performed. However, this also carries a risk of perforating the bladder wall, creating the ideal circumstances to facilitate peritoneal or abdominal metastases. Small, asymptomatic bladder perforations occur frequently and are associated with gender: female, decreasing body mass index, higher tumour stage, deeper infiltration and higher resection weight. Since many of these perforations are extraperitoneal, heal spontaneously and do not elicit any significant perioperative symptoms, they remain undiagnosed. Even in cases of intraperitoneal perforation, peritoneal tumour recurrence has been rarely reported. We report on the unusual case of a 61-year-old woman who underwent TURBT for non-muscle invasive urothelial carcinoma that was complicated by intraperitoneal bladder perforation requiring open repair.